A comparison of sinusoidal, square wave, sawtooth, and staircase forms of transient ramped voltammetry when a reversible process is analysed in the frequency domain - Gavaghan, D; Elton, D; Bond, A (2001)
Sawtooth and squarewave forms of transient voltammetry have been simulated in order that a detailed comparison with results previously undertaken on sinusoidal and square wave forms of voltammetry could be made in the frequency domain. All theoretical calculations were performed for a reversible process, assuming a linear dc ramped potential is present, and using numerical simulations which were analysed using the fast Fourier transform method. On the basis of this study, the conclusion is reached that transient voltammetric methods, where a periodic signal is superimposed onto a dc potential, are part of a family of techniques having essentially common characteristics, which can all be analysed in a unified theoretical framework, in contrast to current practice of treating them in inherently different manners. The subtle differences that arise are related to the non-linear effects encountered when large amplitudes of the periodic waveform are superimposed onto the dc potential. Experimental data on the oxidation of ferrocene in acetonitrile support the fidelity of the simulations of sawtooth voltammetry. © 2001 Published by Elsevier Science B.V.